NON-APPROVED INDICATION USE OF CYPROHEPTADINE AND ITS IMPLICATIONS FOR PATIENT SAFETY AND REGULATION - Shabrina Adinda Septiarani; Arya Gading Purwanto; Vivi Septiani Putri; Nabilah Siti Zahara; Alisha Dian Prasasti; Karina Insanillahiya; Kannaya Sabriena Keenan Iswanto; Aisyah Humairah; Primayanti Nurul Ilmi (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2025)
Cancer related anorexia and cachexia significantly impair nutritional status, quality of life, and treatment outcomes. While appetite stimulants like megestrol acetate and dronabinol have shown effectiveness, their adverse effects limit long-term use. Cyproheptadine, a first-generation antihistamine and serotonin antagonist, has emerged as a potentially safer alternative. This review aims to evaluate critically synthesize previous research findingson clinical studies, randomized trials, and retrospective analyses on cyproheptadine’s efficacy and safety as an appetite stimulant. It has shown consistent benefits across various populations, including children with cystic fibrosis, patients with nonorganic failure to thrive, and adults with cancer-related cachexia. Improvements include significant appetite score increases (e.g., K-ESAS change of –2.42 vs. –2.03 with placebo; p = 0.0307), average weight gains of ~24 g/day, and improved BMI and nutritional markers such as albumin and hemoglobin. The most common side effect was mild drowsiness, while serious adverse effects like hepatotoxicity were rare. However, concerns remain about off-label overuse in community settings, often due to lack of patient education and regulatory oversight. Overall, cyproheptadine appears to be an effective and well-tolerated short-term option for appetite stimulation. Nonetheless, more research is needed to establish long-term safety, efficacy, and appropriate dosing guidelines.